Endoscopic papillary large balloon dilation without sphincterotomy for users of antithrombotic agents: A multicenter retrospective study. Issue 3 (7th February 2019) - Hakuta, Ryunosuke; Kogure, Hirofumi; Nakai, Yousuke; Hamada, Tsuyoshi; Noguchi, Kensaku; Saito, Kei; Saito, Tomotaka; Takahara, Naminatsu; Mizuno, Suguru; Yagioka, Hiroshi; Ito, Yukiko; Tada, Minoru; et al.
Abstract : Background and Aim: With an aging population, an increasing number of individuals on antithrombotic agents are diagnosed with large bile duct stones. Studies have shown the effectiveness of endoscopic papillary large balloon dilation (EPLBD) for removal of large bile duct stones. EPLBD without endoscopic sphincterotomy (EST) may reduce the risk of procedure‐related bleeding, but the safety of this procedure for users of antithrombotic agents remains unclear. Methods: In this multicenter retrospective study, we included patients who underwent EPLBD without EST for bile duct stones between March 2008 and December 2017. We compared adverse events and other clinical outcomes between users and non‐users of antithrombotic agents (antiplatelet agents and anticoagulants). Results: We analyzed a total of 144 patients (47 users and 97 non‐users of antithrombotic agents). Among the users, the agents were continued in 13% and were replaced with heparin in 62% during the periprocedural period. We did not observe clinically significant bleeding and thrombotic events irrespective of the use of antithrombotic agents. Overall rate of early adverse events did not differ between users and non‐users (6.4% and 7.2%, P = 0.99). Procedural outcomes did not differ between the groups (necessity for lithotripsy, 28% vs. 29%; and complete stone removal in a single session, 72% vs. 71%, for users and non‐users, respectively). Conclusions: Endoscopic papillary large balloon dilation without EST may be done without a substantial increase in procedure‐related bleeding for users of antithrombotic agents. A larger study is required to refine the management strategy for those agents during the periprocedural period.